Acehnese interference in students' spoken Arabic: A multi-level cross-linguistic analysis in an Indonesian Islamic boarding school - Maulana Ihsan Ahmad; Hisyam Zaini; Windi Alhafiza Rambe (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
Although numerous studies have examined Arabic language interference among Indonesian learners, detailed analyses integrating multiple linguistic levels within a single Acehnese-speaking institutional context remain a significant gap in the literature. This study addresses that gap by investigating cross-linguistic influence in students’ spoken Arabic at Dayah Babul Maghfirah, an Islamic boarding school in Aceh that formally enforces Arabic-only communication. Adopting a qualitative descriptive approach, the study analyzes naturally occurring oral interactions collected through non-participant observation over one week. Data were examined using Miles, Huberman, and Saldaña’s interactive model. The findings reveal systematic Acehnese interference across four linguistic levels: 1) phonological substitutions of marked Arabic consonants; 2) morphological projection of Acehnese particles and affixes; 3) syntactic transfer of Acehnese-dominant structural templates; and 4) lexical insertion of discourse markers and interjections. These patterns demonstrate that local linguistic repertoires remain structurally active even within immersion-oriented institutional settings, challenging assumptions that policy-driven environments suppress first-language influence. By providing a systematic multi-level mapping of interference within a single pesantren environment, this study contributes empirically to cross-linguistic influence research and extends Indonesian interference scholarship to an underrepresented regional context. The findings offer evidence-based insight for Arabic pedagogy in multilingual religious education settings where immersion policies coexist with deeply entrenched vernacular linguistic identities.